2022
DOI: 10.3390/su142315592
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Factors Affecting Environmental Pollution for Sustainable Development in the Future—The Case of Vietnam

Abstract: In many studies in Vietnam, the scientists only focus on economic growth and attracting foreign direct investment. Environmental pollution has not been paid much attention in Vietnam. Therefore, this paper aims to identify the factors affecting environmental pollution in Vietnam. The author gathered the annual information based on World Bank data from 2000 to 2022. Data were processed via STATA 16.0; linear regression was used in this research. The results show that renewable consumption, economic growth and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Thu et al investigated the factors that contribute to environmental pollution in Asia and Vietnam. They found that the greater the renewable consumption is, the better the environmental condition has in Vietnam and Asia [22,23]. Raihan et al referred to the connections that exist between green electricity consumption, the industrialization of the economy, forest area coverage, and CO2 in the Russian context [24,25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thu et al investigated the factors that contribute to environmental pollution in Asia and Vietnam. They found that the greater the renewable consumption is, the better the environmental condition has in Vietnam and Asia [22,23]. Raihan et al referred to the connections that exist between green electricity consumption, the industrialization of the economy, forest area coverage, and CO2 in the Russian context [24,25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thu et al studied the Factors Affecting Environmental Pollution for Sustainable Development Goals—Evidence from Asian Countries. They focus on the renewable energy can promote the sustainable and green economy in Asia [ 49 , 50 ].…”
Section: Literature Reviewmentioning
confidence: 99%